2020
DOI: 10.1038/s41396-020-0665-8
|View full text |Cite
|
Sign up to set email alerts
|

Combining whole-genome shotgun sequencing and rRNA gene amplicon analyses to improve detection of microbe–microbe interaction networks in plant leaves

Abstract: Microorganisms from all domains of life establish associations with plants. Although some harm the plant, others antagonize pathogens or prime the plant immune system, support the acquisition of nutrients, tune plant hormone levels, or perform additional services. Most culture-independent plant microbiome research has focused on amplicon sequencing of the 16S rRNA gene and/or the internal transcribed spacer (ITS) of rRNA genomic loci, which show the relative abundance of the microbes to each other. Here, we de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(111 citation statements)
references
References 76 publications
(98 reference statements)
1
109
0
1
Order By: Relevance
“…AmpStop can also be used by researchers who do choose PNAs, as blocking oligos design essentially follows the same procedure 16 . Studies of leaves of the wild plant A. thaliana found that bacterial fraction of extracted DNA are typically very low but range up to about 25% 20 . We found that more blocking cycles (15 vs. 10) were necessary to efficiently block non-target amplification in real leaf samples, but not in mock communities with 5% bacterial DNA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AmpStop can also be used by researchers who do choose PNAs, as blocking oligos design essentially follows the same procedure 16 . Studies of leaves of the wild plant A. thaliana found that bacterial fraction of extracted DNA are typically very low but range up to about 25% 20 . We found that more blocking cycles (15 vs. 10) were necessary to efficiently block non-target amplification in real leaf samples, but not in mock communities with 5% bacterial DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Some host amplification can be advantageous because it can be used to quantitatively estimate bacterial loads 18 and having quantitative information has can change inferred ecological relationships between plant microbiota 20 . When we only blocked chloroplast in the 16S V3/V4 region and allowed mitochondrial amplification, the fraction of bacterial reads was proportional to the bacterial DNA load in mock communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…wild Arabidopsis thaliana leaves (Regalado et al 2020). From these samples, we detect 37 different eukaryotic species and 25 different eukaryotic families (Table S7) We apply the EukDetect pipeline to public datasets from the human gut microbiome and the plant leaf microbiome, detecting eukaryotes uniquely present in each environment.…”
Section: Eukaryotes In the Plant Leaf Microbiomementioning
confidence: 99%
“…DNA and RNA sequencing from the IHMP IBDMDB project was downloaded from the NCBI SRA under Bioproject PRJNA398089 (Lloyd-Price et al 2019). Sequencing data from the Arabidopsis thaliana leaf microbiome was downloaded from the European Nucleotide Archive under accession PRJEB31530 (Regalado et al 2020).…”
Section: Analysis Of Public Datasetsmentioning
confidence: 99%